Examination of pathways involved in leukemia inhibitory factor (LIF)-induced cell growth arrest using label-free proteomics approach - Ali, Syed Azmal; Kaur, Gurjeet; Kaushik, Jai Kumar; Malakar, Dhruba; Mohanty, Ashok Kumar; Kumar, Sudarshan (Journal of proteomics, 2017)
Leukemia inhibitory factor (LIF) is a multifunctional highly glycosylated protein, synthesized and secreted in various body tissues. Besides the abundance in multiple organs, the molecular mechanism underlying the LIF interactions for cell survival and polarity is poorly understood. In the present study, high-resolution LC-MS/MS based LFQ approach identified 2083 proteins with the overall PSM as 16,032. This proteomics data reviles that LIF promotes the AKT-mTOR signaling pathway. It induces cell growth arrest by an intracellular pathways loop to increase the half-life of the cell. Bioinformatics-based enrichment analysis revealed the involvement of LIF interacting partners in cell survival through increasing the cell cycle length. The anti-proliferative effect of LIF was confirmed by BrdU, MTT and Caspase 3/7 assays and further validated by RT-qPCR. Till date to the best of our knowledge, this is the first study that elucidates LIF-mediated cascade of activation of MEK/ERK, Ras, mTOR, Hippo, and RAP1 pathways. This study further expands the repertoire of signaling pathways known to be subject to activation by LIF. These multiple involvements of pathways through autocrine-paracrine mediated cell cycle arrest additionally suggests a novel means for amplification of a growth arrest stimulus from LIF and its homolog's receptors. Leukemia inhibitory factor (LIF) is the polyfunctional cytokine and highly pleiotropic member of the interleukin-6 family. It utilizes a receptor that consists of the LIF receptor b and gp130 and displays diverse effects on target cells. Despite well-known signal transduction mechanisms (JAK/STAT, MAPK, and PI3K) LIF also contains paradoxically opposing influences in several cell types which includes cellular stimulation, inhibition, proliferation, differentiation, and survival. LIF1 is also undergoing clinical trials as a driving force for the embryo implantation in the uterus in women who fail to become pregnant. As LIF can act on the broad spectrum of cell types, it is necessary to understand the basic response mechanism. The available non-canonical regulatory pathways and molecular mechanism associated with LIF are poorly explained. Therefore, we have performed the global proteome analysis of LIF-mediated autocrine-paracrine signaling. The obtained data were examined through advanced bioinformatics tools and LIF inducible changes in terms of pathways were elucidated. The result showed the involvement of cluster of proteins maintaining the Ras/Rap1/STAT3/Hippo pathways which modify the protein component machinery of core histone complexes. This report describes the involvement of proteins responsible for cell growth and progression and defines the LIF-mediated novel autocrine-paracrine signaling loop for cell growth arrest. [Display omitted] •Expression of LIF responsible for the of functionally differentiated structures.•Proteomic analysis has been conducted to analyze the proteins expression pattern of signaling pathways.•A total of 630 non-redundant differentially expressed proteins with≥1.5 of 347 up-regulated and ≤0.66 of 200 down-regulated proteins were identified with ≥95 % confidence interval.•The identified differential expressed proteins are responsible for the induction of JAK/STAT3, PI3K/AKT, MAPK, ERK1/2, Ras, AKT-mTOR, Hippo, and RAP1 signaling pathways.•This study projects the involvement of multiple pathways through autocrine-paracrine mediated cell cycle arrest through STAT3 dependent and independent growth arrest stimulus from LIF and its homolog’s receptors.